Brain Arterial Diameters as a Risk Factor for Vascular Events. Issue 8 (August 2015) - Gutierrez, Jose; Cheung, Ken; Bagci, Ahmet; Rundek, Tatjana; Alperin, Noam; Sacco, Ralph L.; Wright, Clinton B.; Elkind, Mitchell S. V.
Abstract : Background: Arterial luminal diameters are routinely used to assess for vascular disease. Although small diameters are typically considered pathological, arterial dilatation has also been associated with disease. We hypothesize that extreme arterial diameters are biomarkers of the risk of vascular events. Methods and Results: Participants in the Northern Manhattan Study who had a time‐of‐flight magnetic resonance angiography were included in this analysis (N=1034). A global arterial Z ‐score, called the brain arterial remodeling (BAR) score, was obtained by averaging the measured diameters within each individual. Individuals with a BAR score <−2 SDs were considered to have the smallest diameters, individuals with a BAR score >−2 and <2 SDs had average diameters, and individuals with a BAR score >2 SDs had the largest diameters. All vascular events were recorded prospectively after the brain magnetic resonance imaging. Spline curves and incidence rates were used to test our hypothesis. The association of the BAR score with death ( P =0.001), vascular death ( P =0.02), any vascular event ( P =0.05), and myocardial infarction ( P =0.10) was U‐shaped except for ischemic stroke ( P =0.74). Consequently, incidence rates for death, vascular death, myocardial infarction, and any vascular event were higher in individuals with the largest diameters, whereas individuals with the smallest diameters had a higher incidence of death, vascular death, any vascular event, and ischemic stroke compared with individuals with average diameters. Conclusions: The risk of death, vascular death, and any vascular event increased at both extremes of brain arterial diameters. The pathophysiology linking brain arterial remodeling to systemic vascular events needs further research.